PENGARUH PENGUNGKAPAN CSR, TIMELINESS, PROFITABILITAS, PERTUMBUHAN PERUSAHAAN DAN RESIKO SISTEMATIK TERHADAP EARNING RESPONSE COEFFICIENT (ERC) (Studi Empiris Pada Perusahaan Manufaktur, Properti dan Pertambangan yang Terlisting di Bursa Efek Indonesia (BEI) pada periode 2013-2014) - Muhamad Fauzan; Agus Purwanto (Diponegoro Journal of Accounting, 2017)
This objective of this research is to examine the influence of corporate social responsibility disclosure, timeliness, profitability, growth and systematic risk (beta) toward firm’s earning response coefficient. The population in this study consist of manufacturing, mining and property companies listed in Indonesian Stock Exchange in the year 2013-2014. A total sample of 306 companies were used in this study as determined by purposive sampling method. The data used is secondary data. Data analysis was performed with descriptive statistics, classical assumption and hypothesis testing of regression method using SPSS 21. The empirical results of this study show that timeliness, profitability and systematic risk does not have statistically significant influence toward earning response coefficient while corporate social responsibility and growth has significantly positive influence toward earning response coefficient.